The protective effect and diagnostic performance of NOX‐5 in Crimean‐Congo haemorrhagic fever patients. Issue 4 (April 2018) - Büyüktuna, Seyit Ali; Doğan, Halef Okan; Bakir, Mehmet; Elaldi, Nazif; Gözel, Mustafa Gökhan; Engin, Aynur
Abstract : Introduction. : Crimean‐Congo haemorrhagic fever (CCHF) is an acute viral haemorrhagic disease. Reactive oxygen species that are mainly generated by the nicotinamide adenine dinucleotide phosphate (NADPH) oxidase (NOX) enzyme family have a pivotal role in the pathophysiology of many diseases. The serum levels of NOX isoforms in patients with CCHF have yet to be assessed. Methods. : This prospective study was conducted at Cumhuriyet University, Turkey. Only patients with CCHF confirmed by the National Reference Virology Laboratory were enrolled in the study. The study subjects comprised 67 CCHF patients and 70 healthy control subjects. The quantitative sandwich ELISA technique was used for the determination of serum NOX 1, 2, 4 and 5. Results. : Higher median median NOX‐1 ( P =0.001) and NOX‐5 ( P <0.001) levels were found in patients compared to the control group. Higher median serum NOX‐5 levels were found in the low‐grade disease group compared to the intermediate‐high disease group according to two different severity scores ( P =0.003). Negative correlations were also found between the serum NOX‐5 levels and the severity scores [( P <0.05, r =‐0.259), ( P <0.01, r =‐0.417)]. The area under the curve (AUC) values for the NOX‐1 and NOX‐5 were 0.67 (confidence interval: 0.58‐0.75) and 0.99 (confidence interval: 0.95‐1.00), respectively. Lower NOX‐5 levels were found in patients receiving thrombocyte suspension ( P =0.004) Conclusions. : NOX‐5 may have a protective effect on CCHF patients and the measurement of serum NOX‐5 levels may be used as a novel biochemical test in the diagnosis of CCHF.